Experiential Learning on Distance Education - Varol, Nurhayat (Acad Conferences Ltd, 2011)
Distance education is a teaching method which usage has increased rapidly on the last few decades. The most advantages of the distance education are to be independent from the place and time. Especially for the people who have a job, distance education offers a good opportunity to last lifelong education for everybody. Thanks to rapid developed information technology there are some new methods used by teaching for technical courses as a distance. Multimedia is a flexible and creative teaching tool that supports distance education. Using simulation and animation by course materials on virtual environment enable for the students to follow technical courses like robotics. Experienced learning can be explained as a teaching method where the students act the real roles. They learn doing experiment on the computer screen. Experiential learning is a knowledge management of the human capital. To catch the success a team work is necessary for teaching a technical course online. Human capital is a potential of the competences, knowledge and personality attributes for offering a technical course online. A team work is necessary for preparing a learning strategy based on experiential learning. The main target on experienced learning is to be able to create a bridge between human capital and knowledge management. We have taught robotics course online since 2001 at Firat University. At that time some people bearded this method because they adduced that it will not be possible to teach a technical subject as a distance. We prepared all course materials online supported by animation and simulation. Students experienced course contents on virtual environment. We followed the success of all students who have taken robotics courses online. We built an institution called Distance Education Center where human capital was evaluated and a creative knowledge management applied. In this paper experiential learning methods that applied at Firat University are discussed. The organization applied on human capital was evaluated and findings are criticized and finally some recommendations are offered for the management of the human capitals by robotics course.
8th International Conference on Intellectual Capital, Knowledge Management and Organisational Learning (ICICKM) -- OCT 27-28, 2011 -- Bangkok Univ, Inst Knowledge & Innovat SE Asia (IKI-SEA), Bangkok, THAILAND
Keywords: distance education; online course; robotics; technology related courses